2008
DOI: 10.1053/j.gastro.2008.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Aminotransferase Levels and 20-Year Risk of Metabolic Syndrome, Diabetes, and Cardiovascular Disease

Abstract: Background & Aims-Nonalcoholic fatty liver disease (NAFLD) is the hepatic manifestation of obesity and metabolic syndrome. Alanine aminotransferase (ALT) levels are used to detect NAFLD and have also been associated with increased risk for metabolic syndrome, diabetes mellitus and cardiovascular disease. We studied the relationship between ALT levels and these disorders in a long-term follow-up study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
233
1
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(260 citation statements)
references
References 55 publications
16
233
1
10
Order By: Relevance
“…A recent large, national, population-based study has shown an association between trunk fat accumulation and increased ALT levels and has indicated the possibility that liver injury can be induced by metabolically active intraabdominal fat (46). ALT levels have been associated closely with the development of incident metabolic syndrome and type 2 diabetes (47). Notably, we show here that galantamine treatment of obese mice significantly suppressed serum ALT levels and liver enlargement to levels determined in lean mice.…”
Section: G a L A N T A M I N E T R E A T M E N T A T T E N U A T E S supporting
confidence: 54%
“…A recent large, national, population-based study has shown an association between trunk fat accumulation and increased ALT levels and has indicated the possibility that liver injury can be induced by metabolically active intraabdominal fat (46). ALT levels have been associated closely with the development of incident metabolic syndrome and type 2 diabetes (47). Notably, we show here that galantamine treatment of obese mice significantly suppressed serum ALT levels and liver enlargement to levels determined in lean mice.…”
Section: G a L A N T A M I N E T R E A T M E N T A T T E N U A T E S supporting
confidence: 54%
“…Up to the present, a numbers of studies have conducted the prospective relationship between liver enzymes and risk of MS, but they have been predominantly performed in American and European populations (9)(10)(11)(12); only, a limited number of prospective studies have been performed in Asian populations. For example, Suzuki et al (13) studied the serial order of elevated ALT with features of MS and showed that elevated ALT is preceded by weight gain, whereas the other features followed the elevated ALT.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it is unavoidable that a large number of asymptomatic workers with elevated ALT (e-ALT), regardless of the underlying cause, are asked do rotating shift work (RSW) on 24-h production lines [3] . In previous studies, e-ALT [4,5] and shift work [6,7] had been independently assessed for their associations with metabolic syndrome (MetS), which has been linked with cardiovascular disease (CVD) [8,9] , one of the leading death causes among working populations [10] . However, for early middle-aged workers with e-ALT in baseline conditions, few longterm follow-up studies assessed the association between RSW and MetS development.…”
Section: Introductionmentioning
confidence: 99%